2022
DOI: 10.1200/op.21.00046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Palliative Care Nurse Practitioner in an Oncology Clinic: A Quality Improvement Effort

Abstract: PURPOSE: Guidelines support early integration of palliative care (PC) into standard oncology practice; however, little is known as to whether outcomes can be improved by modifying health care delivery in a real-world setting. METHODS: We report our 6-year experience of embedding a nurse practitioner in an oncology clinic (March 2014-March 2020) to integrate early, concurrent advance care planning and PC. RESULTS: Compared with patients with advanced cancer not enrolled in the palliative care nurse practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…These activities, albeit important, could be delegated to other team members freeing the study nurses to focus on issues that require skilled nursing, such as nonpharmacologic symptom or stress management. 32 The study findings align with several other studies supporting nurses' impact on delivering specific domains of primary palliative care. Houben and colleagues 15 tested the effect of a 1.5-hour nurse-led ACP intervention among patients with chronic obstructive pulmonary disease on quality of patient-clinician communication, prevalence of ACP discussions 6 months post intervention, and anxiety and depression in patients and their loved ones.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These activities, albeit important, could be delegated to other team members freeing the study nurses to focus on issues that require skilled nursing, such as nonpharmacologic symptom or stress management. 32 The study findings align with several other studies supporting nurses' impact on delivering specific domains of primary palliative care. Houben and colleagues 15 tested the effect of a 1.5-hour nurse-led ACP intervention among patients with chronic obstructive pulmonary disease on quality of patient-clinician communication, prevalence of ACP discussions 6 months post intervention, and anxiety and depression in patients and their loved ones.…”
Section: Discussionsupporting
confidence: 89%
“…Although the nurses had access to social workers, they felt compelled to help patients in the moment. These activities, albeit important, could be delegated to other team members freeing the study nurses to focus on issues that require skilled nursing, such as nonpharmacologic symptom or stress management 32 …”
Section: Discussionmentioning
confidence: 99%
“…Embedded PC clinic models aim to improve PC delivery by decreasing patient appointment burden, 16 facilitating earlier palliative referrals, 11 and shortening the lag time between PC referral and first palliative clinic appointment. 17 Building on prior studies that have shown the positive effects of embedded clinics on PC delivery, [10][11][12]17 this study further characterizes the changes in referral patterns and palliative referral completion when implementing an embedded PC clinic model among patients with advanced thoracic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated the feasibility of embedded palliative clinic models in both academic and private practice oncology clinics. [10][11][12] The availability of specialty-trained PC clinicians remains the rate-limiting step for palliative clinic development, while understanding the effect of expanded outpatient palliative resources on patient access and referral patterns is an area of future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation